The Dose Rate of Corpuscular Ionizing Radiation Strongly Influences the Severity of DNA Damage, Cell Cycle Progression and Cellular Senescence in Human Epidermoid Carcinoma Cells - Sergey S. Soroko; Dmitry V. Skamnitskiy; Ekaterina N. Gorshkova; Olga M. Kutova; Ismail R. Seriev; Anna V. Maslennikova; Evgeniy L. Guryev; Sergey V. Gudkov; Vladimir A. Vodeneev; Irina V. Balalaeva; Natalia Yu Shilyagina (Current Issues in Molecular Biology)
Modern radiotherapy utilizes a broad range of sources of ionizing radiation, both low-dose-rate (LDR) and high-dose-rate (HDR). However, the mechanisms underlying specific dose-rate effects remain unclear, especially for corpuscular radiation. To address this issue, we have irradiated human epidermoid carcinoma A431 cells under LDR and HDR regimes. Reducing the dose rate has lower lethality at equal doses with HDR irradiation. The half-lethal dose after HDR irradiation was three times less than after LDR irradiation. The study of mechanisms showed that under HDR irradiation, the radiation-induced halt of mitosis with the accompanying emergence of giant cells was recorded. No such changes were recorded after LDR irradiation. The level of DNA damage is significantly greater after HDR irradiation, which may be the main reason for the different mechanisms of action of HDR and LDR irradiations. Comparing the mechanisms of cell response to LDR and HDR irradiations may shed light on the mechanisms of tumor cell response to ionizing radiation and answer the question of whether different dose rates within the same dose range can cause different clinical effects.